Adipose stem cell‐derived extracellular matrix represents a promising biomaterial by inducing spontaneous formation of prevascular‐like structures by mvECs. Issue 10 (15th July 2020) - Nellinger, Svenja; Schmidt, Isabelle; Heine, Simon; Volz, Ann‐Cathrin; Kluger, Petra J.
Abstract: Tissue constructs of physiologically relevant scale require a vascular system to maintain cell viability. However, in vitro vascularization of engineered tissues is still a major challenge. Successful approaches are based on a feeder layer (FL) to support vascularization. Here, we investigated whether the supporting effect on the self‐assembled formation of prevascular‐like structures by microvascular endothelial cells (mvECs) originates from the FL itself or from its extracellular matrix (ECM). Therefore, we compared the influence of ECM, either derived from adipose‐derived stem cells (ASCs) or adipogenically differentiated ASCs, with the classical cell‐based FL. All cell‐derived ECM (cdECM) substrates enabled mvEC growth with high viability. Prevascular‐like structures were visualized by immunofluorescence staining of endothelial surface protein CD31 and could be observed on all cdECM and FL substrates but not on control substrate collagen I. On adipogenically differentiated ECM, longer and higher branched structures could be found compared with stem cell cdECM. An increased concentration of proangiogenic factors was found in cdECM substrates and FL approaches compared with controls. Finally, the expression of proteins associated with tube formation (E‐selectin and thrombomodulin) was confirmed. These results highlight cdECM as promising biomaterial for adipose tissue engineering by inducing the spontaneous formation of prevascular‐like structures by mvECs. Abstract : In vitro vascularization remains a major challenge in tissue engineering. In this study, we evaluated the ability of cell‐derived extracellular matrix (cdECM) derived from the stem cell stage and the adipogenic stage of adipose‐derived stem cells, to induce the spontaneous formation of prevascular‐like structures by microvascular endothelial cells. Cytocompatibility, degree of structure formation, and expression of vascular‐associated proteins were analyzed. Results revealed cdECM as a promising material for prevascularization.